Diagnostico situacional de la inseguridad en el crecimiento turístico del Parque Lineal de la Parroquia San Camilo año 2021 - Vera Arana, Judith del Pilar (2021)
The present research work took place in the Quevedo canton in which the situational analysis and study of the causes and problems of tourist insecurity was carried out in the attractiveness of the linear park of the San Camilo parish, in order to find a solution to the Security problems being the most prominent, social security such as crime in the sector, drugs, robberies, and little culture in social security issues. Physical security related to the protection owed by the people who visit the attraction. That is why the objective of this research to diagnose the insecurity factors that influence the sector for the development of tourist security strategies that can be implemented for the tourist growth of the linear park in order to promote it as a safe place and thus increase the influx of tourists who visit the place who can be sure of going to the attraction, since constant police controls will be taken, so that they feel safe and go with their family and Friends. This research was carried out by applying a descriptive research as a methodology, in the same way, surveys were carried out that helped to verify that most of the people who visit the attraction believe that safety influences a lot when visiting the linear park of the San Camilo Parysh.